Activation of the EIF2AK4-EIF2A/eIF2α-ATF4 pathway triggers autophagy response to Crohn disease-associated adherent-invasive Escherichia coli infection. Issue 5 (3rd May 2016) - Bretin, Alexis; Carrière, Jessica; Dalmasso, Guillaume; Bergougnoux, Agnès; B'chir, Wafa; Maurin, Anne-Catherine; Müller, Stefan; Seibold, Frank; Barnich, Nicolas; Bruhat, Alain; Darfeuille-Michaud, Arlette; Nguyen, Hang Thi Thu
ABSTRACT: The intestinal mucosa of Crohn disease (CD) patients is abnormally colonized by adherent-invasive E. coli (AIEC). Upon AIEC infection, autophagy is induced in host cells to restrain bacterial intracellular replication. The underlying mechanism, however, remains unknown. Here, we investigated the role of the EIF2AK4-EIF2A/eIF2α-ATF4 pathway in the autophagic response to AIEC infection. We showed that infection of human intestinal epithelial T84 cells with the AIEC reference strain LF82 activated the EIF2AK4-EIF2A-ATF4 pathway, as evidenced by increased phospho-EIF2AK4, phospho-EIF2A and ATF4 levels. EIF2AK4 depletion inhibited autophagy activation in response to LF82 infection, leading to increased LF82 intracellular replication and elevated pro-inflammatory cytokine production. Mechanistically, EIF2AK4 depletion suppressed the LF82-induced ATF4 binding to promoters of several autophagy genes including MAP1LC3B, BECN1, SQSTM1, ATG3 and ATG7, and this subsequently inhibited transcription of these genes. LF82 infection of wild-type (WT), but not eif2ak4 −/−, mice activated the EIF2AK4-EIF2A-ATF4 pathway, inducing autophagy gene transcription and autophagy response in enterocytes. Consequently, eif2ak4 −/− mice exhibited increased intestinal colonization by LF82 bacteria and aggravated inflammation compared to WT mice. Activation of the EIF2AK4-EIF2A-ATF4 pathway was observed in ileal biopsies from patients with noninflamed CD, and this was suppressed in inflamed CD, suggesting that a defect in the activation of this pathway could be one of the mechanisms contributing to active disease. In conclusion, we show that activation of the EIF2AK4-EIF2A-ATF4 pathway upon AIEC infection serves as a host defense mechanism to induce functional autophagy to control AIEC intracellular replication.